2006
DOI: 10.1016/j.vaccine.2005.11.019
|View full text |Cite
|
Sign up to set email alerts
|

Integration and expression of Bluetongue VP2 gene in somatic embryos of peanut through particle bombardment method

Abstract: After pre-culture and treatment of osmosis, zygotic embryos of peanut (Arachis hypogaea L.) were transformed via particle bombardment with a plasmid containing a Bluetongue VP2 gene (BTVP2) comprising neutralizing epitopes. Selection for Kanamycin resistant calluses and somatic embryos was initiated at 12th day post-bombardment on medium containing 25 mg/L Kanamycin. Under continuous selection, 12.38% Kanamycin resistant plantlets were regenerated from bombarded somatic embryos. The presence and integration of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 15 publications
1
5
0
Order By: Relevance
“…Athmaram et al (2006) described a protocol for the genetic transformation of peanut or groundnut (Arachis hypogaea) using immature zygotic embryos bombarded with tungsten microparticles coated with a binary plasmid carrying BTVP2 gene (pCAMBIABTVP2) encoding the major antigenic determinants of Bluetongue (BT) disease caused by a double-stranded RNA virus (Orbivirus genus), which affects primarily sheeps, but also goats, cattle, and wild ruminants. Transgene integration into the plastid genome was demonstrated by PCR.…”
Section: Particle Bombardment-mediated Transformationmentioning
confidence: 99%
“…Athmaram et al (2006) described a protocol for the genetic transformation of peanut or groundnut (Arachis hypogaea) using immature zygotic embryos bombarded with tungsten microparticles coated with a binary plasmid carrying BTVP2 gene (pCAMBIABTVP2) encoding the major antigenic determinants of Bluetongue (BT) disease caused by a double-stranded RNA virus (Orbivirus genus), which affects primarily sheeps, but also goats, cattle, and wild ruminants. Transgene integration into the plastid genome was demonstrated by PCR.…”
Section: Particle Bombardment-mediated Transformationmentioning
confidence: 99%
“…The expression and inheritance study for RPVH demonstrated stable integration in T 1 generation plants, which have been used for the oral administration of cattle for vaccination resulting into hemagglutinin-specific antibody production (Khandelwal et al, 2003b). Further, BTV-VP2 (bluetongue VP2 gene) has also been expressed in peanut for resistant to bluetongue virus (BTV) which is a causal agent of bluetongue of disease of sheep (Athmaram et al, 2006). Recently, HN gene expressing hemagglutininneuraminidase protein of Peste des petits ruminant virus (PPRV) in peanut plants has also been tested for oral administration in vaccination of sheep (Khandelwala et al, 2011).…”
Section: Oral Vaccinementioning
confidence: 99%
“…Southern blot analysis revealed that transgenic plants regenerated after two subcultures of cell lines on selective medium with 350 mg L −1 spectinomycin showed heteroplasmy (presence of wild-type and transformed chloroplast genome), whereas those recovered after eight to ten subcultures of the cell lines were homoplasmic. Athmaram et al (2006) described a protocol for the genetic transformation of peanut or groundnut (Arachis hypogaea) using immature zygotic embryos bombarded with tungsten microparticles coated with a binary plasmid carrying BTVP2 gene (pCAMBIABTVP2) encoding the major antigenic determinants of Bluetongue (BT) disease caused by a double-stranded RNA virus (Orbivirus genus), which affects primarily sheeps, but also goats, cattle, and wild ruminants. Pods of the cv.…”
Section: Particle Bombardment-mediated Transformationmentioning
confidence: 99%